Keterbatasan Cerita Pendek Horor Karya Artificial Intelligence (AI) pada Perangkat Lunak ChatGPT - Yudono, Kristophorus Divinanto Adi (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The digital era has given rise to a variety of innovations, one of which is AI. Artificial Intelligence (AI) is assumed to be able to create a variety of things including producing a story. One of the AI known by the public is ChatGPT. However, the production of stories by AI is assumed to have limitations. The purpose of this study is to analyze and describe the limitations of horror short stories produced by the artificial intelligence application, ChatGPT. This research is an objective research by applying a qualitative approach. The source of the research data is 20 horror short stories written by artificial intelligence on the ChatGPT application. Data collection is carried out by listening to record techniques. Data analysis is carried out by structural analysis, which is analyzing the building blocks of the story. This is the basis for conclusions related to the limitations of AI in producing horror stories. The results showed that Ai's limitations in writing horror short stories include limitations in writing titles, conversations, intrinsic elements, and the use of olfactory imagery. AI does not write the title of the story, writes dialogue in the form of direct sentences, repeats the background of the story, and does not write stories with the use of olfactory imagery language style.